2011
DOI: 10.5005/jp-journals-10021-1014
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Cephalometric Measurements with Digital versus Manual Methods

Abstract: Objective: To evaluate the accuracy of measurements obtained with a digital cephalometric software program. Materials and methods: Digital photographs of 32 cephalograms were imported into the Nemotec digital imaging software. Digital measurements of 41 hard and soft tissue variables generated by the software were compared to those obtained by manual tracings. Reproducibility for each method was assessed using Pearson's correlation coefficient by repeating measurements of all radiographs at an interval of 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
2
10
1
Order By: Relevance
“…In the present study, the significant differences found for both Upper and lower lip length (ULL and LLL) supports the findings of Agarwal et al, 18 while contrary to this, Celik et al 6 did not find any significant difference between the two techniques for upper lip length (ULL). The present study showed significant difference for the lower lip protrusion (LLP) between the two techniques, this is corroborated by the findings of Cooke and Wei 23 that lip prominence points are poor landmarks to identify.…”
Section: 313à16supporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the significant differences found for both Upper and lower lip length (ULL and LLL) supports the findings of Agarwal et al, 18 while contrary to this, Celik et al 6 did not find any significant difference between the two techniques for upper lip length (ULL). The present study showed significant difference for the lower lip protrusion (LLP) between the two techniques, this is corroborated by the findings of Cooke and Wei 23 that lip prominence points are poor landmarks to identify.…”
Section: 313à16supporting
confidence: 86%
“…The results of the study showed that the linear measurements i. Gregston et al, 20 Ozsoy et al 12 Contrary to the findings of present study, Uysal et al, 11 Celik et al 6 and Agarwal et al 18 showed significant difference only for U1 to NA, but did not find significant difference for L1 to NB.…”
Section: 313à16contrasting
confidence: 82%
See 1 more Smart Citation
“…They also require lower levels of radiation. 39,40 Hence, digital lateral cephalographs were chosen over manual ones for this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Agarwal et al, 9 very few studies in the literature have been evaluated on soft tissue measurements due to the uncertainty in identifying soft tissue landmarks. Soft tissue cephalometric analysis is gaining popularity, as the orthodontists have understood the importance of soft tissues and their influence on diagnosis and treatment planning.…”
Section: Discussionmentioning
confidence: 99%